อันตรกิริยาของพืชสมุนไพรที่มีฤทธิ์ต้านเบาหวานในพื้นที่ของโครงการอนุรักษ์พันธุกรรมพืช อันเนื่องจากพระราชดำริฯ กับหน้าที่การทำงานของพี-ไกลโคโปรตีน : รายงานวิจัย - สุรีย์ เจียรณ์มงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purpose of this study was to investigate and compare the effects of 4 herbal plants in the plant Genetic Conservation Project area under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn on the expression of P-glycoprotein, using the in vitro model of the Caco-2 cells. The plants were selected into this study by its ability to inhibit α-glucosidase, which is a drug target for diabetic control. These plants included Pterospermum littorale Craib (Family Sterculiaceae); Dialium cochinchinense Pierre (Family Fabaceae); Momecylon plebejum Kurz. Var. ellipsoideum Craib. (Family Metastomataceae) and Thespesia po;ulnae (L.) Soland ex Corr. (Family Malvaceae). The expression of P. glycoprotein was assessed by flow cytometry with the use of a fluorescein isothiocyanate-conjugated anti-human P-gp antibody. The results demonstrated that extracts of M.plebejum and T. populnea at the highest concentration in this study were unable to affect the expression of P-glycoprotein. On the other hand, 3-day exposure of Caco-2 cells with extracts of D. cochinchinense and P. littorale increased the P-glycoprotein expression by approximate 2 folds. The induction effect of P.littorale was concentration dependent. Although the exposure period of Caco-2 cells to all the extracts was extended from 3 days to 7 days, the extent of P-gp expression did not increase correspondingly. The findings suggested that D. Cochinchinense and P. littorale might be able to cause problems regarding P-glycoprotein mediated drug interactions through their ability to increase P-gp expression. Further studies in this regard are needed.